STUDI HASIL TANGKAPAN BYCATCH DAN DISCARD PADA PERIKANAN UDANG MANTIS (Harpiosquilla raphidea) MENGGUNAKAN ALAT TANGKAP GILLNET - Farhan Ramdhani; Nofrizal Nofrizal; Romie Jhonnerie (Bogor Agricultural University, 2019)
Tanjung Jabung Barat Regency has a great potential for mantis shrimp (Harpiosquilla raphidea) resources. This commodity is highly valued, as its price range from Rp. 143,600 to 180,700 for each individual. Annually, the total catches constitute 125,000-225,000 individuals, which become one of export commodities to various countries. In Tanjung Jabung barat, the mantis shrimp has been caught by using gillnet with mesh size of 10 cm. Unfortunately, mantis shrimp fishing deal with a significant number of bycatch and discards, which potentially have negative impact on sustainable fisheries resources. Therefore, the purposes of this study was to emphasis on sustainable fishing effort of mantis shrimp and identify the composition and proportion of bycatch and discards. A series of surveys was conducted for collecting the amount of species caught by gillnet during mantis shrimp fishing operation. The result shows that the bycatch and discards dominated the total catches making up to 54.99% (7 species) and 22.69% (7 species) respectively. Mean while, the total of fishing catches for mantis shrimp was 22.32%.Keywords: bycatch, discards, gillnet, mantis shrimp (Harpiosquilla raphidea)